Polycrystalline SnSe with a thermoelectric figure of merit greater than the single crystal - Zhou, Chongjian; Lee, Yong Kyu; Yu, Yuan; Byun, Sejin; Luo, Zhong-Zhen; Lee, Hyungseok; Ge, Bangzhi; Lee, Yea-Lee; Chen, Xinqi; Lee, Ji Yeong; Cojocaru-Miredin, Oana; Chang, Hyunju; et al. (Nature Publishing Group, 2021)
Thermoelectric materials generate electric energy from waste heat, with conversion efficiency governed by the dimensionless figure of merit, ZT. Single-crystal tin selenide (SnSe) was discovered to exhibit a high ZT of roughly 2.2-2.6 at 913 K, but more practical and deployable polycrystal versions of the same compound suffer from much poorer overall ZT, thereby thwarting prospects for cost-effective lead-free thermoelectrics. The poor polycrystal bulk performance is attributed to traces of tin oxides covering the surface of SnSe powders, which increases thermal conductivity, reduces electrical conductivity and thereby reduces ZT. Here, we report that hole-doped SnSe polycrystalline samples with reagents carefully purified and tin oxides removed exhibit an ZT of roughly 3.1 at 783 K. Its lattice thermal conductivity is ultralow at roughly 0.07 W m(-1) K-1 at 783 K, lower than the single crystals. The path to ultrahigh thermoelectric performance in polycrystalline samples is the proper removal of the deleterious thermally conductive oxides from the surface of SnSe grains. These results could open an era of high-performance practical thermoelectrics from this high-performance material. SnSe has a very high thermoelectric figure of merit ZT, but uncommonly polycrystalline samples have higher lattice thermal conductivity than single crystals. Here, by controlling Sn reagent purity and removing SnOx impurities, a lower thermal conductivity is achieved, enabling ZT of 3.1 at 783 K.